Safe crop protection products - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
Safe and Effective Use of Crop Protection Products in Developing Countries. Edited by J Atkin (Novartis Crop Protection Sector) and K M Leisinger (Novartis Foundation for Sustainable Development), Switzerland. 1999. 192 pp. ISBN 0851994717. £35